Analisis Kebutuhan LKPD Elektronik Materi Perdagangan Internasional Bermodel PBL dan Berorientasi Berpikir Kreatif - Atwano, Siti; Suryani, Erma Aris; Siswanto, Deny Hadi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
This research aims to analyze the need for electronic student worksheets that raise the topic of international trade with a PBL model and are oriented towards creative thinking. This research used a descriptive method by collecting data through interviews, observation, and distributing questionnaires to 30 class XI Social Sciences students at Muhammadiyah Mlati High School. Data analysis uses the Miles and Huberman approach which includes data reduction, data analysis, and conclusion verification. The research results show that: (1) international trade material has the lowest average value and needs improvement; (2) students' creative thinking abilities are still low; (3) the learning applied is still conventional using the lecture method; and (4) students prefer to use electronic student worksheets as open materials. Based on these findings, it can be concluded that students need electronic student worksheets with the topic of international trade with a PBL model and are oriented towards creative thinking skills